Household Management and Women Empowerment in Decision Making: a Spatial Study of Social Disparity in India. - Patra, Aditya Kumar and Acharya, Arabinda (2012)
Daughters are avoided but daughters-in-laws are necessary for family well-being and progeny. This is the dichotomy of our society and it exemplifies the position of women in society. Traditionally men are bread earners and women are engaged in household chores. This is not a stand alone situation in our country, rather it is a worldwide phenomenon. Historically the world over, either by law or by custom, the status of woman is undermined by asymmetrical power relationships in decision making, personal and social rights, access to resources and entitlements. Women are the world‘s largest ‗excluded category‘. However, the concept of the status of women has undergone a great deal of change over the last few decades. ‗Gender Development and Women Empowerment‘ is the catch phrase of the present day world. Factors that lead to gender disparities in many countries include, among others: (i) social institutions such as norms, rights and laws; (ii) household decisions and the resulting resource allocations; and (iii) economic policies that affect the level of household income and its distribution among household members (World Bank 2000). Household as a reckoning unit in the analysis of gender equality occupies an important place. The role of the female member in the household decision making and management carries utmost importance. Hence, Empowerment of Women with respect to household income and decision making is crucial. As a sequel to this an attempt has been made in this paper to examine the ‗Empowerment of Women‘ in household management in our society. Multivariate technique, the ‗Principal Component Analysis‘ is employed towards this end. This write-up attempts to examine the differences in ‗Empowerment of Women‘ of the ‗General Category‘ vis-à-vis the ‗Excluded Groups‘ across the states in Indian economy.